SEKURALITAS DAN SPIRITUALITAS: (Mencari Format dan Integrasi Ilmu untuk Konstruksi Kurikulum Pendidikan Islam) - Asfiati, Asfiati (IAIN Padangsidimpuan, 2014)
Â In order to seek assimilation and renew alintegration intact in the presence of the known integration approaches. Integration used as philosophy that bridges diniyah truths contained in the Scripturesof the Qur'an with scientific truths. The integrationis donein order tofacilitate thesearch for proper formatting and constructionso as to produce works that have ulititas sake better people.The nature ofscience and spirituality in education is taking the value ofthe balance between thephysical, and spiritual fysik, thought and squeezed to gether so as to deliver human well a ligned rationalistic attitude in relation tohis God, with fellow human beings and the natural environment. Sekuralitas as the main idea of reformin Islam that triggered Nurcholish Madjid is dynamic and leads to change. The value of spirituality in clued the desire for a meaning full ife (the will to meaning) that motivates human life to always look for the meaning of life (the meaning of life) and crave meaning ful life (the meaning ful life).Islamic Education curriculum is used as a tool or instrument to educate students in developing potential ruhiyah jismiyah and that they later were able to recognize and affirm syahadah primordial back to Allah. The curriculum is good and relevant in order to achieve the objectives of Islamic education is to be integrated and comprehensive, covering general science and religion, as well as make the Qur'an and Hadith as the primary source of Islamic education through the analysis of the concept of research methods (philosophical), historical research methods and action research methods (action).